Representation type of Schur algebras - Doty, SR; Erdmann, K; Martin, S; Nakano, D (1999)
We give a complete classification of the classical Schur algebras and the infinitesimal Schur algebras which have tame representation type. In combination with earlier work of some of the authors on semisimplicity and finiteness, this completes the classification of representation type of all classical and infinitesimal Schur algebras in all characteristics.